U.S. Men's Perceptions and Experiences of Emergency Contraceptives. (May 2017) - Wright, Rachel L.; Fawson, Peter R.; Frost, Caren J.; Turok, David K.
Research suggests that men should be included in reproductive health decision making to help enhance positive health outcomes for their partners. Men affect the use of contraception and what method is used. Men's decisions may be affected by different factors such as gender, education, and the nature of their sexual relationship. A qualitative study was conducted to explore males' experiences and perceptions about emergency contraception (EC), and the meanings males assign to EC. Semistructured in-depth focus groups were held with 15 men who engage in heterosexual activity recruited from a university setting in the United States. Participants expressed egalitarian views of the contraception decision-making processes, a sense of responsibility regarding reproductive decision making, and that society has a negative stigma toward those who use EC. However, there was a lack of knowledge regarding the copper intrauterine device, which was not viewed as a method of EC. Exploring the role and needs of men in reproductive health care discussions and research is an important and growing area. Recommendations are provided for health care practitioners, policy, and future research around men and EC.